Odpowiedzi

2010-03-11T15:35:30+01:00
A) 5x+10= 5(x+2)
b) -3p-5r= -(3p+5r)
c) -6x+4= -2(3x-2)
d) -12a-8= -4(3a+2)
e) 3ab+4a= a(3b+4)
f) 5a-10ab= 5a(1-2b)
g) -2xyz-xz= -xz(2y+1)
h)3k(do potęgi2) - k2= k(3k-k)
1 1 1
Najlepsza Odpowiedź!
2010-03-11T15:37:16+01:00
A) 5x+10=5(x+2)
b) -3p-5r=-(3p+5r)
c) -6x+4=-2(3x-2)
d) -12a-8=-4(3a+2)
e) 3ab+4a=a(3b+4)
f) 5a-10ab=5a(1-2b)
g) -2xyz-xz=-xz(2y+1)
h)3k(do potęgi2) - k2=k(3k-k)
2010-03-11T15:38:36+01:00
A) 5x+10=..5..(x+2)
b) -3p-5r=-(..3p..+..5r..)
c) -6x+4=-2(.3...x-...2.)
d) -12a-8=.-4..(3a+2)
e) 3ab+4a=a(.3b..+.4..)
f) 5a-10ab=5a(..1.-..2b.)
g) -2xyz-xz=-xz(.2y..+..1.)
h)3k(do potęgi2) - k2=k(.3k..-.k..)